The Utilization of Family Planning Methods Among Rural Women In Ogun State, Nigeria - Mojisola Oyewole (Research Synergy Foundation, 2020)
Family planning implies spacing and timing of child births. However, despite many actions put in place by government at all levels to sensitize citizen on the need for family planning; most Nigeria population still does not practice it as expected. Thus, the study assessed the utilization of family planning methods among rural women in Ogun State. Multistage sampling technique was used to select 120 respondents and structured questionnaire schedule was used for the data collection. Data collected were analysed using both descriptive and inferential analysis.Result shows that majority of the rural women had mean age of 33±10, 45.0% were Muslims, 57.5% had secondary education, 77.5% married, 50.0% traders, 39.1% had between 5 and 6 persons in their households, 42.5% earned between 35,001 and 60,000 monthly and 66.7% of the were member of social association. Also, 60.8% had low awareness of contraceptive methods. In addition, 56.7% had high knowledge of family planning methods, most of the rural women sourced information on family planning through television. Also, increase in weight experienced by the respondents were the health factors militating against the utilization of family planning methods by the rural women as 50.8% had high utilization of family planning methods used by the rural women. There was a significant relationship between member of social association (?2=4.268, p<0.05), awareness of contraceptive method utilize by rural women (r=0.761, p<0.05), knowledge (r=0.617, p<0.002), source of information (r=-0.119, p<0.05), factors (r=0.201, p<0.05) and level of utilization of family planning methods.It is therefore concluded that most of the women had high knowledge of family planning methods but only utilized the commons ones available to them. It is therefore recommended that educative trainings should be organized for the women to enhance their usage of other methods to ensure a secured child bearing.